Pacific Lamprey Translocations to the Snake River Boost Abundance of All Life Stages. Issue 3 (23rd April 2022) - Hess, Jon E.; Delomas, Thomas A.; Jackson, Aaron D.; Kosinski, Michael J.; Moser, Mary L.; Porter, Laurie L.; Silver, Greg; Sween, Tod; Weitkamp, Laurie A.; Narum, Shawn R.
Abstract: The Pacific Lamprey Entosphenus tridentatus is an anadromous fish that has severely declined in the Snake River basin. In 2007, the Nez Perce Tribe initiated translocation of adults to this region from the main‐stem Columbia River and has continued the translocations to this day. These actions are aimed at restoring larval abundance along with holistic habitat improvements. We performed parentage and sibship analyses with 260 single‐nucleotide polymorphism loci to monitor productivity of translocated lamprey over a decade (2007–2018). These results provide the first direct evidence that translocations boosted larval abundance, increased juvenile production in the interior Columbia River ( 3% in 2017 and 2018), and demonstrated successful migration to the Pacific Ocean. Per capita juvenile production from Snake River adult lamprey translocations out‐performed that of their volitionally migrating counterparts in the interior Columbia River, demonstrating that translocating adults to suitable habitats increased overall productivity. We projected that the translocations may eventually return enough adult offspring to the Columbia River to replace the annual take of adults for translocations, despite many adults likely returning to other basins. These translocations are also restoring Pacific Lamprey to historical areas where they had been nearly extirpated, which has impactful benefits both culturally and ecologically. Further, this study provided an unprecedented volume of data that has redefined key biological attributes, including timing of life stage transformation (average of 6.7‐year‐old juveniles), larval growth rates ( 22 mm/year for the first 4 years), ocean duration (average of 5.1 years), dispersal ( 3% of Snake River‐origin adults that return to the Columbia River will divert to the Willamette River), and life span (median age of postspawn adults was 12.9 years). We even quantified a new biological phenomenon of delayed spawning, which occurs at low rates ( 9%) in nature. These data provide an opportunity to monitor ongoing translocation efforts and inform adaptive management to aid species recovery.